Impact of AGT rs5050(T>G) variants on associations between estradiol and angiotensinogen levels: Multi-Ethnic Study of Atherosclerosis (MESA) - Karita C. F. Lidani; Patrick J. Trainor; Shubham Tomar; Erin D. Michos; Erin S. Morgan; Jerome I. Rotter; Xiuqing Guo; Sotirios Tsimikas; Andrew P. DeFilippis (PLoS ONE, 2025)
Aims Angiotensinogen plays an essential role in maintaining circulatory homeostasis. AGT rs5050(T > G) has been identified as a regulator of the transcription of AGT mRNA, with differential expression between sexes. We sought to determine if rs5050(T > G), an estrogen response element, modifies the relationship between estrogen and angiotensinogen levels. Methods rs5050(T > G) was genotyped, and plasma angiotensinogen levels were measured in 4,831 MESA participants, including postmenopausal women, on hormone therapy (n = 709) or not (n = 1,551), and 2,581 men. Linear regression models were employed to determine the associations of angiotensinogen with rs5050(T > G) allele dosage; and to evaluate whether rs5050(T > G) modifies the association between estradiol and angiotensinogen, with a main effect term and interaction term between rs5050(T > G)*estradiol. Estimated marginal means (EMMs) were used to further evaluate the effect of estradiol on angiotensinogen across different rs5050 alleles (T > G). Results rs5050 TT had the highest median levels of angiotensinogen, followed by TG and GG . Adjusted main effect model showed positive associations between estradiol and angiotensinogen, with each rs5050 T allele associated with 0.329 SD higher log-angiotensinogen levels (CI 95% 0.293, 0.365). The interaction rs5050(T > G)*estradiol was not significant, with EMMs exhibiting overlapping slope confidence intervals across genotypes. The proportion of the variance in angiotensinogen explained by modeling increases from 47.9% to 51.6% when including rs5050(T > G) or interation rs5050(T > G)*estradiol in the model. Conclusions rs5050(T > G) is associated with circulating angiotensinogen levels, but rs5050(T > G) alleles do not influence the relationship between estradiol and angiotensinogen. This suggests that estrogen’s effect on angiotensinogen regulation occurs independently of rs5050(T > G), despite its location within an estrogen-responsive element.